Dry-milled flour rice ‘Seolgaeng’ harbors a mutated fructose-6-phosphate 2-kinase/fructose-2,6-bisphosphatase2 - Kang, Ju-Won; Lee, Sang-Kyu; Shim, Su-Hyeon; Shin, Dongjin; Cho, Jun-Hyeon; Lee, Ji-Yoon; Ko, Jong-min; Ji, Hyeonso; Park, Hyang-Mi; Ahn, Eok-Keun; Lee, Jong-Hee; Jeon, Jong-Seong (Frontiers in Plant Science, 2023)
‘Seolgaeng’, an opaque-endosperm rice (Oryza sativa) mutant, is used to prepare high-quality dry-milled rice flour. The mutation causing its opaque-endosperm phenotype was unknown. Map-based cloning identified a missense mutation in the gene FRUCTOSE-6-PHOSPHATE 2-KINASE/FRUCTOSE-2,6-BISPHOSPHATASE 2 (OsF2KP2) in Seolgaeng. Transfer DNA insertion and clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated nuclease 9 (Cas9)-induced f2kp2 mutants exhibited opaque endosperm. Rice harbors another F2KP gene, OsF2KP1. CRISPR/Cas9-induced double mutants of OsF2KP1 and OsF2KP2 (f2kp-d) possessed more opaque endosperm compared to f2kp2 single mutants, whereas the endosperm of the f2kp1 single mutant was normal. Grain hardness and damaged starch content were significantly reduced in f2kp2 mutants compared to the wild type and f2kp1. Amylose content was lower than normal in f2kp2 mutants but not f2kp1. Grain hardness and amylose content were much lower in f2kp-d than in f2kp2. Starch polymerization analysis revealed altered amylopectin structure in f2kp2 and f2kp-d mutants. F2KP activity was lower in f2kp2 and much lower in the double mutants when compared to the wild types, but f2kp1 showed no significant difference. In coleoptiles, hypoxia induced OsF2KP2 expression but downregulated OsF2KP1. These results suggest that OsF2KP2 functions as the main F2KP isoform in endosperm experiencing hypoxia, but OsF2KP1 may partially compensate for the absence of OsF2KP2. We propose that F2KP has a crucial role in inorganic pyrophosphate-utilizing energy metabolism for starch biosynthesis in rice endosperm.